If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-6(-6p-6)=-144
We move all terms to the left:
-6(-6p-6)-(-144)=0
We add all the numbers together, and all the variables
-6(-6p-6)+144=0
We multiply parentheses
36p+36+144=0
We add all the numbers together, and all the variables
36p+180=0
We move all terms containing p to the left, all other terms to the right
36p=-180
p=-180/36
p=-5
| X/4=7w | | 243^(2x-6)=9^(x+1) | | 4.3s+8.61=9.73+5.1s | | 39=7y | | -3-147=-6(-7-8r) | | 12.56-g=9 | | 1n-4n+3=-30 | | 7=2x+4x+16 | | 3(5b+6)=-102 | | 155=2x | | w+1.4=5.72 | | X+3=4x+11 | | 4(5-5a)=-100 | | 90=6(4m-1) | | -8+5(x-8)+2x=-10 | | -140-15=5(5+9b) | | 9.95-0.7z=-9.85-4.3z | | (-2)(x)=-2x* | | -4-5(1-4m)=71 | | 6(x-2)+12=18 | | 4y-6=2y+40 | | 8p-6=-2(-4p+1) | | 3=p−91/2 | | 3(2x-8)-7=-73 | | 4x^2=53.3*(0.5-x)^2 | | -112=4(-3+5z) | | 2.5(6.25x+0.5)=11 | | 10-10p=-8-10+4p | | 59=9+5y | | (3)(x)=2x | | 34x–68=0 | | 11x=-9+2+x=-199 |